PESAN KOMUNIKASI DALAM MEMBANGUN PERILAKU RAMAH LINGKUNGAN (Studi Kasus pada Komunitas Pulo Geulis di Kota Bogor) - Megafirmawanti Lasinta; Yoenita Jayadisastra; Hartina Batoa (Universitas Halu Oleo, 2022)
Messages in a communication process can influence a person in making decisions, whether or not to perform certain behaviors. One of the important things to study is how the community treats their environment. This study aims to analyze how the use of message frames in building an environmentally friendly community and how the level of environmentally friendly behavior in the community. The location of this research is in a densely populated communities in the city of Bogor, namely Pulo Geulis which is located in the middle of the Ciliwung river. Data collection and analysis has been carried out since 2019 using a research instrument in the form of a questionnaire. The results showed that the types of message frames used in building environmentally friendly behavior were benefit messages, risk messages, and technical messages. The level of environmentally friendly behavior of Pulo Geulis residents is at the level of